(untitled) (Nonlinear Studies, 2023)
This paper investigates the existence of weak solutions for a Dirichlet boundary value problem of p(x)-Kirchhoff type driven by p(x)-Laplacian-like operators, arising from the capillarity phenomena. The existence is proved by using the topological degree for a class of demicontinuous operators of generalized (S_+) type and the theory of variable-exponent Sobolev spaces. Our result extends some recent work in the literature.